Personalizirani pristopi v klinični biokemiji in laboratorijski medicini - Marc, Janja (Farmacevtski vestnik, 2020)
Recently, personalised approaches in the treatment of several chronic diseases such as cancer, osteoporosis, autoimmune and joint diseases are being translated from the research to the clinical practice. The goal of the personalised medicine is individualisation of therapy to achieve its optimal efficiency and safety. Laboratory medicine professionals play a key role in this process, since they provide the information needed to optimize the therapy. Researchers at the Chair of Clinical Biochemistry and Laboratory Medicine have been developing several fields of personalised (or precision) medicine, such as pharmacogenomics, nutrigenomics and cell ther-persoapy, in the context of various diseases, such as acute lymphoblastic leukaemia, chronic lymphocytic leukaemia, osteoporosis, degenerative joint disease and autoimmune diseases. Further translation of these approaches into clinical practice depends on the level of education of health professionals in this field. Thus, the incorporation of these topics into study programs is of the utmost importance.
Keywords: Avtoimunske bolezni; Degenerativne bolezni; degenerativne bolezni sklepov; Levkemija; Osteoporoza; Personalizirana medicina